Stage, stake, and scaffold humans and animals in Shakespeare's theatre - d (Oxford : Oxford University Press, 2011)
In Shakespeare's London, the stage of the playhouse, the stake of the bear baiting arena, and the scaffold of public execution constituted an ensemble of related spectacles that shared the same audiences. Andreas Hofele argues that this generated a powerful exchange of images and a spill-over of animal features into Shakespeare's characters.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Shakespeare, William, -- 1564-1616 -- Knowledge -- Animals; Theater -- England -- History -- 17th century